2015
DOI: 10.1371/journal.pone.0138217
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Childhood Home Environment to Cortical Thickness in Late Adolescence: Specificity of Experience and Timing

Abstract: What are the long-term effects of childhood experience on brain development? Research with animals shows that the quality of environmental stimulation and parental nurturance both play important roles in shaping lifelong brain structure and function. Human research has so far been limited to the effects of abnormal experience and pathological development. Using a unique longitudinal dataset of in-home measures of childhood experience at ages 4 and 8 and MRI acquired in late adolescence, we were able to relate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 35 publications
2
37
0
1
Order By: Relevance
“…Studies investigating low cognitive stimulation have also been mixed. While one study found that low cognitive stimulation was associated with thinner cortex in the frontoparietal network across childhood and adolescence (Rosen et al, 2018), another found that lower cognitive stimulation was associated with thicker cortex in the lateral prefrontal cortex and ventral visual stream in late adolescents (Avants et al, 2015).…”
Section: Ela and Brain Developmentmentioning
confidence: 99%
“…Studies investigating low cognitive stimulation have also been mixed. While one study found that low cognitive stimulation was associated with thinner cortex in the frontoparietal network across childhood and adolescence (Rosen et al, 2018), another found that lower cognitive stimulation was associated with thicker cortex in the lateral prefrontal cortex and ventral visual stream in late adolescents (Avants et al, 2015).…”
Section: Ela and Brain Developmentmentioning
confidence: 99%
“…The stimulation of sensorimotor abilities in the first years of life seems to be crucial for the development of subsequent cognitive skills (Hernandez & Caçola, 2015;Tierney & Nelson, 2009). Several factors may have an effect in cognitive development, such as low birth weight; respiratory, neurological, and cardiovascular disorders; neonatal infections; malnutrition; low socioeconomic status; and prematurity, for example (Avants et al, 2015;Greenough & Black, 2013;Handal et al 2007). The more negative factors in the children's life, the more likely the damages in their development (Evans & Fuller-Rowell, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…First, there are genetic factors that may determine at least a significant amount of those cognitive skills and deficits (Krapohl et al, 2014), and it may vary from children to children. Then, there are other variables that can be involved such as distinct pedagogical practice approach from different schools (Bondy et al 2007;Challen et al 2014;Malti et al 2011), parenting style (Karbach et al 2013;Lugo-Gil & Tamis-LeMonda, 2008), and environmental nurturing (Avants et al, 2015;McEwen, 2012). Some mechanisms of resilience may underline these results as well (Chen et al, 2012;Hutz et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, such an environment includes parental behaviors that encourage children to engage in enriching activities as well as to learn new skills (e.g., colours, new words, shapes, sizes, and spatial relations; Bradley & Caldwell, ). Similar aspects of the home environment were also conceptualized in the literature as “home learning environment” (e.g., Schmiedeler et al, ; Sylva, Melhuish, Sammons, Siraj‐Blatchford, & Taggart, ) and “environmental stimulation” (Avants et al, ). Such a home environment has been previously investigated in relation to poverty and SES (e.g., Guo & Harris, ; Votruba‐Drzal, ), intellectual development (e.g., Guo & Harris, ), and children's executive functions (e.g., Clark et al, ).…”
Section: Introductionmentioning
confidence: 94%